St Benedict's Priory, Saint-Malo, 1611–1669. Issue 4 (October 2017) - Scott, Geoffrey
Over the last few years, the 400th anniversaries of the foundations of three of the earliest monasteries of the revived English Benedictine Congregation have been celebrated: St Gregory's, Douai (1606), St Laurence's, Dieulouard (1608) and St Edmund's, Paris (1615). There have been no similar celebrations for the one monastery which did not survive, that of St Benedict in Saint-Malo, which was founded in 1611 and ended its days as an English Benedictine monastery in 1669, when it was handed over to the French Congregation of Saint-Maur. This article is a delayed attempt to record briefly the story of the priory of St Benedict in Saint-Malo.